Ink composition and laminate
Patent Information
- Application Number
- JP2025057846
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-03-31
AI Technical Summary
【0009】 本発明によれば、優れた耐摩擦性を有し、保温性にも優れる印刷塗膜を形成可能なインキ組成物、及び前記インキ組成物を用いて形成された印刷層を有する積層体を提供できる。
Smart Images

Figure 2026165456000004 
Figure 2026165456000005 
Figure 2026165456000001
Abstract
Description
Technical Field
[0001] The present invention relates to an ink composition and a laminate.
Background Art
[0002] Various objects around us, including food, daily necessities, and industrial materials, are subjected to printing processing with ink for displaying decorations and product information. As such an ink, for example, Patent Document 1 discloses a liquid printing ink containing a binder resin, an organic solvent, and a specific isocyanate compound.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] In recent years, characteristic functions are often required for ink coating films, going beyond mere decoration and display of product information. The inventors of the present application conducted studies to impart further different functions to printed coating films. Specifically, studies were conducted on an ink composition capable of forming a printed coating film with excellent heat retention. Since a printed coating film is generally a thin film compared to a substrate to be printed, or a container, molded body or the like on which the printed matter is used, it is known that it is extremely difficult to develop effective heat retention. The heat retention of the printed coating film formed from the liquid printing ink described in Patent Document 1 is not sufficient.
[0005] Furthermore, abrasion resistance is one of the physical properties normally required for a printed coating film. Since printed matter with a printed coating film is constantly exposed to opportunities for contact and friction with all kinds of objects, from the printing process to subsequent processing steps, transportation, display, and use by consumers, it is very important that the printed coating film can withstand friction.
[0006] The inventors of this application conducted research and found that it is extremely difficult to obtain an ink composition that yields a printed coating film with excellent heat retention and abrasion resistance.
[0007] The present invention aims to provide an ink composition capable of forming a printed coating film that has excellent abrasion resistance and excellent heat retention, and a laminate having a printed layer formed using the ink composition. [Means for solving the problem]
[0008] The present invention has the following aspects. [1] An ink composition comprising a binder resin (A) and a pyrolysis-type foaming agent (B), wherein the pyrolysis-type foaming agent (B) comprises a pyrolysis-type foaming main agent (B-1), and the solid content of the pyrolysis-type foaming agent (B) relative to the total mass of solid content of the ink composition is 5 to 65% by mass, and the binder resin (A) comprises a (meth)acrylic resin (A1), and the solid content of the resin having a softening temperature of 70°C or less relative to the total mass of solid content of the binder resin (A) is 50% by mass or less. [2] The ink composition according to [1] further comprising a curing agent. [3] The ink composition according to [1] or [2], wherein the average particle size of the thermal decomposition type foaming agent (B-1) is 20 μm or less. [4] The ink composition according to any one of [1] to [3], further comprising a hydrocarbon wax. [5] An ink composition according to any one of [1] to [4], which is for gravure printing or flexographic printing. [6] A laminate comprising a plastic film and a printed layer formed on one surface of the plastic film using an ink composition according to any one of [1] to [5]. [7] The laminate according to [6], wherein the printed layer is a printed layer in which the thermal decomposition type foaming agent (B) has not decomposed and foamed. [8] The laminate according to [6], wherein the printed layer is a printed layer obtained by decomposing and foaming the thermal decomposition type foaming agent (B). [Effects of the Invention]
[0009] According to the present invention, it is possible to provide an ink composition capable of forming a printed coating film that has excellent abrasion resistance and excellent heat retention, and a laminate having a printed layer formed using the ink composition. [Brief explanation of the drawing]
[0010] [Figure 1] This is a schematic cross-sectional view showing an example of the laminate of the present invention. [Figure 2] This is a schematic cross-sectional view showing an example of the laminate of the present invention. [Modes for carrying out the invention]
[0011] The present invention will now be described in detail. The following embodiments are merely illustrative for illustrating the present invention and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various forms without departing from its spirit.
[0012] The definitions of terms used in this specification are as follows: The softening point of the binder resin can be measured by the ring-and-ball method in accordance with JIS K 5601-2-2:1999. A thermal decomposition type foaming agent is a substance that decomposes and foams when heated. The average particle size of the thermal decomposition type foaming agent is the volume-based cumulative 50% particle size, measured by laser diffraction / light scattering. The decomposition temperature of a pyrolysis-type blowing agent can be measured by thermogravimetric analysis. Specifically, the pyrolysis-type blowing agent is heated at a constant rate under an inert gas atmosphere, and the temperature at which weight loss begins can be defined as the decomposition temperature. If the pyrolysis-type blowing agent contains a pyrolysis-type blowing aid as described below, the mixture of the pyrolysis-type blowing main agent and the pyrolysis-type blowing aid is measured as the pyrolysis-type blowing agent. A "unit" is a general term for atomic groups derived from one monomer molecule, which are directly formed by the polymerization of monomers, and atomic groups obtained by chemically transforming a part of the above atomic group. Note that "units based on monomers" are sometimes simply called "monomer units." For example, "units based on (meth)acrylic acid esters" are also called "(meth)acrylic acid ester units." "(Meth)acrylic" is a general term for "acrylic" and "methacrylic". "Variable component" refers to volatile components such as water and organic solvents. Specifically, it refers to components other than the solid components listed below (volatile components). The "solid content" of an ink composition refers to the components of the ink composition excluding the medium, and is the component that ultimately forms the coating layer. Specifically, it is measured in accordance with JIS K 5601-1-2:2008. Note that solid content is also called non-volatile content. "Printed coating film" refers to the coating film formed by the ink composition of the present invention. The weight-average molecular weight of the binder resin is the weight-average molecular weight converted to the standard polystyrene molecular weight and is measured by gel permeation chromatography (GPC). The glass transition temperature of the binder resin is measured in accordance with JIS K 7121:2012 as follows: Using a differential scanning calorimeter, 10 mg of the binder resin is heated from -100°C to 160°C at a rate of 20°C / min. The glass transition temperature is determined from the intersection point of the baseline and the tangent to the endothermic curve in the resulting curve (DSC curve). The hydroxyl value of the binder resin is measured in accordance with JIS-K 1557-1:2007. The acid value of the binder resin is expressed in milligrams as the amount of potassium hydroxide required to neutralize acidic groups such as carboxyl groups per gram of non-volatile matter in the sample, and is measured in accordance with JIS K 5601-2-1:1999. The "~" symbol indicating a numerical range means that the numbers before and after it are included as the lower and upper limits, respectively.
[0013] Ink Composition An ink composition according to an embodiment of the present invention comprises a binder resin (A) and a thermally decomposable foaming agent (B). The ink composition may further contain components other than the binder resin (A) and the thermally decomposable foaming agent (B) (hereinafter also referred to as "optional components") as necessary, within a range that does not impair the effects of the present invention.
[0014] <Binder Resin (A)> The binder resin (A) used in the present invention includes a (meth)acrylic resin (A1). Further, other resin (A2) may be used in combination within a range that does not impair the effects of the present invention. The (meth)acrylic resin (A1) is not a resin having a softening temperature of 70°C or lower.
[0015] ((Meth)acrylic Resin (A1)) The (meth)acrylic resin (A1) used in the present invention is a resin containing a (meth)acrylate ester unit as a main component. Examples of the (meth)acrylic resin (A1) include a homopolymer of one type of (meth)acrylate ester; a copolymer of two or more types of (meth)acrylate esters; a copolymer of a (meth)acrylate ester and another monomer copolymerizable with the (meth)acrylate ester; a (meth)acrylic urethane resin; and a silicone-modified (meth)acrylic resin, and the like. Each of the above (meth)acrylate esters and other monomers may be used singly or in combination of two or more. As the (meth)acrylic resin (A1), one type may be used alone, or two or more types may be used in combination.
[0016] Examples of (meth)acrylic acid esters include, but are not limited to, alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; aryl (meth)acrylates such as phenyl (meth)acrylate and naphthyl (meth)acrylate; and hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate.
[0017] Other monomers mentioned above include, but are not limited to, styrene monomers such as styrene, α-methylstyrene, vinyltoluene, and their derivatives; unsaturated carboxylic acid monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid; and acrylamide, methacrylamide, acrylonitrile, and methacrylonitrile.
[0018] The content of (meth)acrylic acid ester units relative to the total mass of (meth)acrylic resin (A1) is preferably 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.
[0019] The hydroxyl value of the (meth)acrylic resin (A1) is preferably 1 to 150 mg KOH / g, more preferably 1 to 130 mg KOH / g, and particularly preferably 1 to 100 mg KOH / g. If the hydroxyl value of the (meth)acrylic resin (A1) is below the lower limit, the adhesion of the resulting printed coating to the substrate tends to decrease. If the hydroxyl value of the (meth)acrylic resin (A1) exceeds the upper limit, the blocking resistance of the resulting printed coating tends to decrease. In addition, the stability of the ink composition tends to decrease.
[0020] The acid value of the (meth)acrylic resin (A1) is preferably 100 mg KOH / g or less, more preferably 30 mg KOH / g or less, and particularly preferably 20 mg KOH / g or less. The lower limit of the acid value of the (meth)acrylic resin (A1) is not particularly limited, but for example, it is preferably 0.1 mg KOH / g or more, more preferably 0.5 mg KOH / g or more, and even more preferably 1 mg KOH / g or more. If the acid value of the (meth)acrylic resin (A1) exceeds the above upper limit, the stability of the ink composition tends to decrease.
[0021] The glass transition temperature of the (meth)acrylic resin (A1) is preferably 5°C or higher, more preferably 10°C or higher, and particularly preferably 15°C or higher. The upper limit of the glass transition temperature of the (meth)acrylic resin (A1) is not particularly limited, but for example, it is preferably 110°C or lower, more preferably 100°C or lower, and even more preferably 90°C or lower. If the glass transition temperature of the (meth)acrylic resin (A1) is below the above lower limit, the heat retention, blocking resistance, and heat resistance of the resulting printed coating tend to decrease.
[0022] The weight-average molecular weight of the (meth)acrylic resin (A1) is preferably 10,000 to 300,000, more preferably 15,000 to 280,000, and particularly preferably 20,000 to 250,000. If the weight-average molecular weight of the (meth)acrylic resin (A1) is below the lower limit, the blocking resistance and heat resistance of the resulting printed coating tend to decrease. If the weight-average molecular weight of the (meth)acrylic resin (A1) exceeds the upper limit, the adhesion of the resulting printed coating to the substrate tends to decrease.
[0023] The solid content of (meth)acrylic resin (A1) relative to the total mass of solid content of binder resin (A) is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. If the content of (meth)acrylic resin (A1) is below the above lower limit, the heat retention and abrasion resistance of the resulting printed coating tend to decrease.
[0024] (Other resins (A2)) The ink composition of this embodiment may contain other resins (A2) to suit various required physical properties, as long as they do not impair the effects of the present invention. The other resins (A2) are not particularly limited as long as they are compatible with the (meth)acrylic resin (A1), but examples include polyurethane resins, vinyl chloride-vinyl acetate copolymers, polyester resins, cellulose derivatives, epoxy resins, polyamide resins, terpene resins, rosin derivatives, and chlorinated polyolefin resins. Other resins (A2) may be used individually or in combination of two or more types.
[0025] The softening temperature of the other resin (A2) is not particularly limited, and any can be used. However, if the other resin (A2) with a softening temperature of 70°C or lower is included, the content of the other resin (A2) with a softening temperature of 70°C or lower relative to the total mass of solids in the binder resin (A) is 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less. If the content of other resins (A2) with a softening temperature of 70°C or lower exceeds the above upper limit, the heat retention, heat resistance, and abrasion resistance of the resulting printed coating tend to decrease, and the heat-resistant adhesion tends to deteriorate.
[0026] (Polyurethane resin) Polyurethane resin is a resin obtained by polymerizing a polyol compound and a polyisocyanate compound. Polyurethane resin can be produced by conventionally known methods. For example, a urethane prepolymer can be obtained by reacting a polyol compound and a diisocyanate compound, and the obtained urethane prepolymer can be reacted with either or both a chain extender and / or a reaction inhibitor as needed.
[0027] Examples of diisocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-xylylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4-diisocyanate, 2,2-diphenylpropane-4,4-diisocyanate, 3,3-dimethyldiphenylmethane-4,4-diisocyanate, 4,4-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene Examples include aromatic diisocyanates such as n-1,4-diisocyanate, naphthylene-1,5-diisocyanate, and 3,3-dimethoxydiphenyl-4,4-diisocyanate; aliphatic diisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate, norbornane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. Diisocyanate compounds may be used individually or in combination of two or more.
[0028] Examples of polyol compounds include polyester polyols, polycarbonate polyols, and polyether polyols. Polyol compounds may be used individually or in combination of two or more.
[0029] Examples of polyester polyols include polyester polyols or polyesteramide polyols obtained by a dehydration polycondensation reaction between polycarboxylic acids and polyhydric alcohols or secondary to tertiary amines. Specific examples of polycarboxylic acids include succinic acid, adipic acid, sebacic acid, azelaic acid, terephthalic acid, isophthalic acid, orthophthalic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, hexahydroorthophthalic acid, naphthalenedicarboxylic acid, and trimellitic acid, as well as their acid esters and acid anhydrides, and one or more of these can be used. Specific examples of polyhydric alcohols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, ethylene oxide or propylene oxide adducts of bisphenol A, trimethylolpropane, glycerin, and low molecular weight alcohol compounds such as pentaerythritol, as well as low molecular weight amino alcohol compounds such as monoethanolamine and diethanolamine, and one or more of these can be used. Specific examples of secondary and tertiary amines include hexamethylenediamine, xylylenediamine, and isophoronediamine, and one or more of these can be used. Furthermore, as polyester polyols, for example, lactone-based polyester polyols obtained by ring-opening polymerization of cyclic ester (lactone) monomers such as ε-caprolactone and γ-valerolactone using low molecular weight alcohol compounds and low molecular weight amino alcohol compounds as initiators can also be used.
[0030] Examples of polycarbonate polyols include those obtained by the dehydrochlorination reaction of a low molecular weight alcohol compound used in the synthesis of polyester polyols with phosgene; and those obtained by the transesterification reaction of this low molecular weight alcohol compound with diethylene carbonate, dimethyl carbonate, diethyl carbonate, and diphenyl carbonate, etc.
[0031] Examples of polyether polyols include polyoxyethylene polyols, polyoxypropylene polyols, polytetramethylene ether polyols, and polyoxyethylene polyoxypropylene polyols, which are obtained by ring-opening polymerization of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide, and tetrahydrofuran, using low molecular weight alcohol compounds, low molecular weight amine compounds, and low molecular weight amino alcohol compounds, as well as phenols, which are used as initiators in the synthesis of polyester polyols. Furthermore, polyester ether polyols obtained by using the aforementioned polyester polyols and polycarbonate polyols as initiators are also included.
[0032] As a chain extender, compounds having two or more functional groups (such as amino groups and hydroxyl groups) that can react with isocyanate groups within the molecule can be used. Examples of chain extenders include diamine compounds such as ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, hexamethylenediamine, isophoronediamine, and 2-ethylaminoethylamine; polyamine compounds such as diethylenetriamine and triethylenetetramine; low molecular weight diol compounds such as ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, and triethylene glycol; and aminoethylethanolamine and aminopropylethanolamine. Chain elongators may be used individually or in combination of two or more.
[0033] Examples of reaction stoppers include monoalkylamines such as n-propylamine and n-butylamine; dialkylamines such as di-n-butylamine; alkanolamines such as monoethanolamine and diethanolamine; and monoalcohols such as methanol and ethanol. Reaction inhibitors may be used individually or in combination of two or more.
[0034] The glass transition temperature of the polyurethane resin is preferably -70 to 0°C, more preferably -60 to -10°C, and even more preferably -50 to -20°C. If the glass transition temperature of the polyurethane resin is below the lower limit, the blocking resistance, heat resistance, and abrasion resistance of the resulting printed coating tend to decrease. If the glass transition temperature of the polyurethane resin exceeds the upper limit, the adhesion and abrasion resistance of the resulting printed coating to the substrate tend to decrease.
[0035] The weight-average molecular weight of the polyurethane resin is preferably 10,000 to 150,000, more preferably 10,000 to 100,000, and particularly preferably 10,000 to 80,000. If the weight-average molecular weight of the polyurethane resin is below the lower limit, the resulting printed coating tends to have reduced blocking resistance, heat resistance, and abrasion resistance. If the weight-average molecular weight of the polyurethane resin exceeds the upper limit, the resulting printed coating tends to have reduced adhesion to the substrate and resistance to rubbing.
[0036] The hydroxyl value of the polyurethane resin is preferably 50 mgKOH / g or less, more preferably 25 mgKOH / g or less, and particularly preferably 10 mgKOH / g or less. The lower limit of the acid value of the polyurethane resin is not particularly limited, but for example, it is preferably 0.1 mgKOH / g or more, more preferably 1 mgKOH / g or more, and even more preferably 3 mgKOH / g or more. If the hydroxyl value of the polyurethane resin exceeds the above upper limit, the blocking resistance and ink stability of the resulting printed coating film tend to decrease.
[0037] The amine value of the polyurethane resin is preferably 10 mg KOH / g or less, more preferably 5 mg KOH / g or less, and particularly preferably 3 mg KOH / g or less. The lower limit of the amine value of the polyurethane resin is not particularly limited, but for example, it is preferably 0.01 mg KOH / g or more, more preferably 0.05 mg KOH / g or more, and even more preferably 0.1 mg KOH / g or more. If the amine value of the polyurethane resin exceeds the above upper limit, its printability tends to decrease.
[0038] The storage modulus (E'; dynamic storage modulus) of the polyurethane resin at a temperature of 100°C and a frequency of 11Hz is preferably 20 MPa or less, more preferably 10 MPa or less, and even more preferably 5 MPa or less. The lower limit of the storage modulus of the polyurethane resin is not particularly limited, but for example, it is preferably 0.1 MPa or more, more preferably 0.5 MPa or more, and even more preferably 1 MPa or more. If the storage modulus of the polyurethane resin exceeds the above upper limit, the adhesion of the resulting printed coating to the substrate tends to decrease. In this specification, the storage modulus is a value obtained by measuring the dynamic viscoelasticity of a printed coating film using a dynamic viscoelasticity measuring device under conditions of a temperature of 100°C and a frequency of 11 Hz.
[0039] The softening temperature of the polyurethane resin is preferably 70 to 180°C, more preferably 90 to 160°C, and even more preferably 100 to 150°C.
[0040] (Vinyl chloride-vinyl acetate copolymer) Vinyl chloride-vinyl acetate copolymers are copolymer products of vinyl chloride and vinyl acetate. Vinyl chloride-vinyl acetate copolymers may also contain monomer units other than vinyl chloride units and vinyl acetate units as needed, and are not particularly limited as long as they are copolymerizable with vinyl chloride and vinyl acetate. Examples of other units include vinyl alcohol units and (meth)acrylate alkyl ester units. Examples of vinyl chloride-vinyl acetate copolymers containing other units include vinyl chloride-vinyl acetate-vinyl alcohol copolymers, vinyl chloride-vinyl acetate-(meth)acrylate hydroxyalkyl ester copolymers, and vinyl chloride-vinyl acetate-dicarboxylic acid copolymers. One of these may be used alone, or two or more may be used in combination. Among these, vinyl chloride-vinyl acetate-vinyl alcohol copolymer resins are preferred.
[0041] The content of vinyl chloride units relative to the total mass of the vinyl chloride-vinyl acetate copolymer is preferably 50 to 98% by mass, more preferably 70 to 98% by mass, and particularly preferably 80 to 95% by mass. If the vinyl chloride unit content is below the lower limit, the blocking resistance of the resulting printed coating tends to decrease. If the vinyl chloride unit content exceeds the upper limit, the adhesion to the substrate and the resistance to rubbing of the resulting printed coating tend to decrease.
[0042] The content of vinyl acetate units relative to the total mass of the vinyl chloride-vinyl acetate copolymer is preferably 0.1 to 20% by mass, more preferably 0.3 to 10% by mass, and particularly preferably 0.5 to 5% by mass. If the vinyl acetate unit content is below the lower limit, the adhesion and abrasion resistance of the resulting printed coating to the substrate tend to decrease. If the vinyl acetate unit content exceeds the upper limit, the blocking resistance of the resulting printed coating tend to decrease.
[0043] The glass transition temperature of the vinyl chloride-vinyl acetate copolymer is preferably 40 to 110°C, more preferably 50 to 100°C, and particularly preferably 60 to 90°C. If the glass transition temperature of the vinyl chloride-vinyl acetate copolymer is below the lower limit, the blocking resistance, abrasion resistance, and heat resistance of the resulting printed coating tend to decrease. If the glass transition temperature of the vinyl chloride-vinyl acetate copolymer exceeds the upper limit, the adhesion of the resulting printed coating to the substrate tends to decrease.
[0044] The number-average molecular weight of the vinyl chloride-vinyl acetate copolymer is preferably 10,000 to 100,000, more preferably 15,000 to 80,000, and particularly preferably 20,000 to 50,000. If the number-average molecular weight of the vinyl chloride-vinyl acetate copolymer is below the lower limit, the blocking resistance, abrasion resistance, and heat resistance of the resulting printed coating tend to decrease. If the number-average molecular weight of the vinyl chloride-vinyl acetate copolymer is above the upper limit, the adhesion of the resulting printed coating to the substrate tends to decrease.
[0045] The softening temperature of the vinyl chloride-vinyl acetate copolymer is preferably 60 to 90°C, more preferably 64 to 80°C, and even more preferably 68 to 75°C.
[0046] <Thermolytic foaming agent (B)> The pyrolysis-type blowing agent (B) comprises a pyrolysis-type foaming main component (B-1). The pyrolysis-type blowing agent (B) may further contain a pyrolysis-type foaming aid (B-2). In one embodiment, it is preferable that the pyrolysis-type blowing agent (B) consists only of the pyrolysis-type foaming main component (B-1). In another embodiment, it is preferable that the pyrolysis-type blowing agent (B) consists only of the pyrolysis-type foaming main component (B-1) and the pyrolysis-type foaming aid (B-2). When the pyrolysis-type foaming agent (B) contains a pyrolysis-type foaming aid (B-2), the ratio of the mass of the pyrolysis-type foaming aid (B-2) to the mass of the pyrolysis-type foaming main agent (B-1) is preferably 0.1 to 0.9, more preferably 0.2 to 0.8, and even more preferably 0.3 to 0.7.
[0047] The decomposition temperature of the thermal decomposition type foaming agent (B) is preferably set appropriately to match the temperature at which the printed coating is heated. The decomposition temperature of the thermal decomposition type foaming agent (B) is preferably 100 to 210°C, more preferably 100 to 180°C, and even more preferably 100 to 150°C.
[0048] (Thermolytic foaming agent (B-1)) The pyrolysis-type foaming agent (B-1) decomposes and foams upon heating. The pyrolysis-type foaming agent (B-1) is broadly classified into organic and inorganic types. Examples of organic pyrolysis-type foaming agents include azo compounds such as azodicarbonamide (ADCA), nitroso compounds such as N,N'-dinitrosopentamethylenetetramine (DPT), hydrazine derivatives such as 4,4'-oxybis(benzenesulfonylhydrazide) (OBSH), semicarbazide compounds, azide compounds, and tetrazole compounds. Examples of inorganic pyrolysis-type foaming agents include bicarbonates, carbonates, and nitrites. Sodium bicarbonate is an example of a carbonate. Among these, organic pyrolysis-type blowing agents are preferred because they exhibit sharp thermal decomposition behavior in response to heating temperature and time, and also have excellent transparency after thermal decomposition. Azodicarbonamide (ADCA), N,N'-dinitrosopentamethylenetetramine (DPT), and 4,4'-oxybis(benzenesulfonyl hydrazide) (OBSH) are particularly preferred from the viewpoint of appropriate decomposition temperature, supply stability, and excellent transparency after thermal decomposition. A single type of thermal decomposition foaming agent may be used alone, or two or more types may be used in combination.
[0049] The average particle size of the pyrolysis-type foaming agent (B-1) is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The lower limit of the average particle size of the pyrolysis-type foaming agent (B-1) is not particularly limited, but for example, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. If the average particle size of the thermal decomposition type foaming agent (B-1) exceeds the above upper limit, the abrasion resistance and storage stability of the resulting printed coating film tend to decrease. Printability also tends to decrease.
[0050] The true specific gravity of the pyrolysis-type foaming agent (B-1) is preferably 2.0 or less, more preferably 1.9 or less, and even more preferably 1.8 or less. The lower limit of the true specific gravity of the pyrolysis-type foaming agent (B-1) is not particularly limited, but for example, it is preferably 1.0 or more, more preferably 1.1 or more, and even more preferably 1.2 or more. If the true specific gravity of the pyrolysis-type foaming agent (B-1) exceeds the above upper limit, its storage stability is likely to decrease. The true specific gravity of the pyrolysis-type foaming agent (B-1) can be measured according to JIS K 0061:2001.
[0051] (Thermolytic foaming agent (B-2)) The pyrolysis-type foaming aid (B-2) adjusts the decomposition temperature of the pyrolysis-type foaming main agent (B-1). Conventional foaming agents can be used, such as urea, urea derivatives, and zinc compounds. Foaming agents may be used individually or in combination of two or more types.
[0052] <Optional ingredients> The ink composition of this embodiment may contain optional components as long as the effects of the present invention are not impaired. Optional components include media, hydrocarbon waxes, pigments, curing agents, fatty acid amides, chelating agents, resin beads, plasticizers, defoamers, dispersants, surfactants, pigment derivatives, anti-settling agents, UV absorbers, antioxidants, antistatic agents, leveling agents, thickeners, and stabilizers. The optional components may be used individually or in combination of two or more.
[0053] (medium) The ink composition of this embodiment may contain a medium. The medium is not particularly limited as long as it can dissolve or stabilize the dispersion of the binder resin (A), and can be appropriately selected depending on the binder resin (A) used. As organic solvents, aromatic organic solvents such as toluene and xylene; aliphatic hydrocarbon organic solvents such as cyclohexane and methylcyclohexane; ketone organic solvents such as methyl ethyl ketone and methyl isobutyl ketone; ester organic solvents such as ethyl acetate, n-propyl acetate, isopropyl acetate, and isobutyl acetate; alcohol organic solvents such as methanol, ethanol, n-propanol, isopropanol, and n-butanol; glycol ether organic solvents such as ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether can be used. As aqueous media, water and mixed media with water-miscible organic solvents can be used.
[0054] In particular, it is environmentally preferable that the product substantially does not contain aromatic organic solvents such as toluene and xylene. Furthermore, depending on the type of pyrolysis-type blowing agent (B), it is preferable that the product does not contain ketone-based organic solvents, as these may impair the stability of the pyrolysis-type blowing agent (B).
[0055] (Hydrogen wax) The ink composition of this embodiment may further contain hydrocarbon wax to improve the blocking resistance and abrasion resistance of the printed coating, to the extent that it does not impair the effects of the present invention. Examples of hydrocarbon waxes include polyethylene wax, Fischer-Tropsch wax, paraffin wax, microstarin wax, and polypropylene wax. Among these, polyethylene wax and Fischer-Tropsch wax are preferred. Examples of polyethylene waxes include high-density polymerized polyethylene, low-density polymerized polyethylene, oxidized polyethylene, acid-modified polyethylene, and special monomer-modified polyethylene. Fischer-Tropsch wax is a wax produced by the Fischer-Tropsch process using carbon monoxide and hydrogen as raw materials, and has a nearly saturated, unbranched, linear molecular structure. Hydrocarbon waxes may be used individually or in combination of two or more types.
[0056] The penetration (hardness) of hydrocarbon wax at 25°C, as specified in JIS K 2207:2006, is preferably 0.1 to 30, more preferably 0.1 to 28, and particularly preferably 0.1 to 25. If the penetration (hardness) of the hydrocarbon wax exceeds the above upper limit, the abrasion resistance of the resulting printed coating tends to decrease. In addition, the printability tends to decrease.
[0057] (Pigment) The ink composition of this embodiment may also contain a pigment. Pigments such as extender pigments, inorganic pigments, and organic pigments can be used. Examples of extender pigments include silica, barium sulfate, kaolin, clay, calcium carbonate, and magnesium carbonate. Examples of inorganic pigments include white pigments such as titanium dioxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, and silica; black pigments such as carbon black and iron black; and various colored inorganic pigments such as aluminum particles, mica, bronze powder, chrome vermilion, lead yellow, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, and zinc oxide.
[0058] Examples of organic pigments include soluble azo, insoluble azo, azo, phthalocyanine, halogenated phthalocyanine, anthraquinone, anthancerone, dianthaquinonyl, anthrapyrimidine, perylene, perinone, quinacridone, thioindigo, dioxazine, isoindolinone, quinophthalone, azomethine azo, flavanthrone, diketopyrrolopyrrole, isoindoline, and indanthrone.
[0059] (Hardening agent) The ink composition of this embodiment preferably contains a curing agent for the purpose of improving the heat retention, adhesion to the substrate, heat resistance, heat adhesion, and abrasion resistance of the resulting printed coating.
[0060] As a curing agent, isocyanate-based curing agents are preferred. An isocyanate-based curing agent is a compound having two or more isocyanate groups in one molecule. Examples of isocyanate-based curing agents include aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI), 2,2'-MDI, 2,4'-MDI, 2,4-tolylene diisocyanate (TDI), 2,6-TDI, m-xylylene diisocyanate (XDI), and 1,4-phenylene diisocyanate; isophorone diisocyanate (IPDI), 1,3-bis(isocyanatomethyl)cyclohexane (hydrogenated XDI), dicyclohexylmethane-4,4'-diisocyanate Examples include alicyclic diisocyanates such as hydrogenated MDI and 1-methylcyclohexane-2,4-diisocyanate (hydrogenated TDI); aliphatic diisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), and 2,4,4-trimethylhexamethylene diisocyanate; and isocyanate prepolymers such as adducts of various diisocyanates, isocyanurates of various diisocyanates, biuret compounds of HDI, and allophanates of HDI. Isocyanate-based curing agents may be used individually or in combination of two or more types.
[0061] <Composition of the ink composition> The solid content of the binder resin (A) relative to the total mass of the ink composition is preferably 5 to 40% by mass, more preferably 8 to 30% by mass, and even more preferably 10 to 25% by mass. The solid content of the binder resin (A) relative to the total mass of solids in the ink composition is preferably 10 to 95% by mass, more preferably 30 to 85% by mass, and even more preferably 35 to 80% by mass. If the solid content of the binder resin (A) is below the lower limit, the adhesion and abrasion resistance of the resulting printed coating to the substrate tend to decrease. Also, the printability tends to decrease. If the solid content of the binder resin (A) exceeds the upper limit, the heat resistance and blocking resistance of the resulting printed coating tend to decrease.
[0062] The solid content of the thermal decomposition type foaming agent (B) relative to the total mass of the ink composition is preferably 0.5 to 30% by mass, more preferably 3 to 20% by mass, and even more preferably 5 to 15% by mass. The solid content of the thermal decomposition type foaming agent (B) relative to the total mass of solids in the ink composition is 5 to 65% by mass, preferably 10 to 60% by mass, and more preferably 20 to 50% by mass. If the content of the thermal decomposition type foaming agent (B) is below the lower limit, the heat retention properties of the resulting printed coating tend to decrease. If the content of the thermal decomposition type foaming agent (B) exceeds the upper limit, the abrasion resistance and adhesion to the substrate of the resulting printed coating tend to decrease.
[0063] The mass ratio of the solid content of the thermal decomposition type foaming agent (B) to the solid content of the binder resin (A) in the ink composition is preferably 0.4 to 20, more preferably 0.5 to 10, and even more preferably 0.6 to 5. The mass ratio of the solid content of the thermal decomposition type foaming agent (B) to the solid content of the (meth)acrylic resin (A1) in the ink composition is preferably 0.3 to 20, more preferably 0.4 to 10, and even more preferably 0.5 to 5.
[0064] When the ink composition contains a medium, the content of the medium relative to the total mass of the ink composition is not particularly limited, but is preferably 10 to 95% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 85% by mass. If the media content is below the lower limit, the ink fluidity and printability of the ink composition tend to decrease. If the media content exceeds the upper limit, the storage stability and printability of the ink composition tend to decrease.
[0065] When the ink composition contains hydrocarbon wax, the solid content of hydrocarbon wax relative to the total mass of the ink composition is preferably 0.01 to 10% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 3% by mass. When the ink composition contains hydrocarbon wax, the content of hydrocarbon wax solids relative to the total mass of solids in the ink composition is preferably 0.1 to 10% by mass, preferably 0.5 to 5% by mass, and more preferably 1 to 3% by mass. If the hydrocarbon wax content is below the lower limit, the blocking resistance and abrasion resistance of the resulting printed coating tend to decrease. If the hydrocarbon wax content exceeds the upper limit, the adhesion of the resulting printed coating to the substrate tends to decrease. In addition, the printability tends to decrease.
[0066] If the ink composition contains a pigment, the pigment content should be set to an amount sufficient to ensure the coloring power of the ink. Specifically, the pigment content relative to the total mass of solids in the ink composition is preferably 1 to 80% by mass, preferably 5 to 60% by mass, and more preferably 10 to 50% by mass.
[0067] When the ink composition contains a curing agent, the solid content of the curing agent relative to the total mass of the ink composition is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, and even more preferably 1 to 3% by mass. When the ink composition contains a curing agent, the content of the curing agent's solids relative to the total mass of the ink composition is preferably 0.1 to 20% by mass, more preferably 1 to 10% by mass, and even more preferably 3 to 8% by mass. If the curing agent content is below the lower limit, the heat retention, adhesion to the substrate, heat resistance, heat adhesion, and abrasion resistance of the resulting printed coating tend to decrease. If the curing agent content exceeds the upper limit, the stability of the ink composition tends to decrease.
[0068] If the ink composition contains any other optional components besides the binder resin (A), the pyrolysis-type foaming agent (B), the medium, the hydrocarbon wax, the pigment, and the curing agent, the solid content of the other optional components relative to the total mass of the ink composition is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and may be 0% by mass. If the ink composition contains any other optional components besides the binder resin (A), the pyrolysis-type foaming agent (B), the medium, the hydrocarbon wax, the pigment, and the curing agent, the content of the solids of the other optional components relative to the total mass of the solids of the ink composition is preferably 25% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0069] <Mechanism of Action> The ink composition of the present invention comprises a (meth)acrylic resin (A1) as a binder resin (A), and further comprises a thermal decomposition type foaming agent (B). In a printed coating formed using the ink composition of the present invention, the thermal decomposition type foaming agent (B) is uniformly dispersed in the binder resin (A) before heat treatment. When the printed coating is heat-treated, the thermal decomposition type foaming agent (B) decomposes and foams, and the areas where the thermal decomposition type foaming agent (B) was present are transformed into bubbles (voids). A printed coating with sufficient bubbles after heat treatment has low thermal conductivity and excellent heat retention properties. On the other hand, in the case of printed coatings that contain a large amount of other resins with a softening temperature of 70°C or lower, it is thought that the bubbles generated by the decomposition and foaming of the thermal decomposition type foaming agent (B) after heat treatment are filled with other resins that have been softened by the heat treatment, and that there are not enough bubbles remaining to exhibit good heat retention. Furthermore, if the amount of thermal decomposition type foaming agent (B) is too low, sufficient bubbles necessary to achieve heat retention will not be generated, and if the amount is too high, the physical properties of the resulting printed coating, such as abrasion resistance and adhesion to the substrate, will decrease. Furthermore, it was discovered that the inclusion of a curing agent in the ink composition causes a cross-linking reaction between resins, preventing the disappearance of air bubbles due to resin softening, and consequently improving the heat retention of the printed coating. It was also found that improvements in coating properties such as abrasion resistance and heat resistance can be expected.
[0070] <Method for manufacturing ink composition> The ink composition of this embodiment can be manufactured, for example, by dissolving or dispersing a binder resin (A), a thermal decomposition type foaming agent (B), and optional components as needed, in a medium. The method of mixing each component is not particularly limited, and the components can be mixed by various methods. The method for dissolving or dispersing each component in the medium is not particularly limited and can be carried out using known dispersers. Examples of dispersers include paint shakers, ball mills, attritors, sand mills, bead mills, dyno mills, roll mills, ultrasonic mills, and high-pressure impact dispersers. In this case, the dispersion process may be performed once or multiple times using one type of disperser, or multiple dispersion processes may be performed using two or more types of dispersers in combination.
[0071] ≪Laminated structure≫ Figures 1 and 2 show an example of a laminate according to one embodiment of the present invention. Note that the dimensional ratios in Figures 1 and 2 differ from those of the actual dimensions for the sake of explanation. The laminate 10 in Figure 1 is a printed material comprising a substrate 11 and a printed layer 12 provided on one surface of the substrate 11. Hereinafter, the printed layer refers to a printed coating. The laminate 20 in Figure 2 is a printed material comprising a base material 21, a first printed layer 22 provided on one surface of the base material 21, and a second printed layer 23 provided on the surface of the first printed layer opposite to the base material. Furthermore, when the laminate is attached to a packaging container as a label, for example, the base materials 11 and 21 may be printed on the inside (the side in contact with the packaging container), i.e., the printing layer 12 and the second printing layer 23 may be printed on the outside, or the printing layer 12 and the second printing layer 23 may be printed on the inside (the side in contact with the packaging container), i.e., the base materials 11 and 21 may be printed on the outside.
[0072] <Base material> The types of base materials 11 and 21 can be appropriately selected according to the types of laminates 10 and 20, etc., and are not particularly limited, but plastic base materials (plastic films) or paper base materials are preferred. Examples of plastic base materials include polyolefins (e.g., polyethylene (PE), polypropylene (PP), etc.), polyesters (e.g., polyethylene terephthalate (PET), etc.), polystyrene (PS), biaxially oriented polypropylene (OPP), unoriented polypropylene (CPP), polycarbonate (PC), polymethyl methacrylate (PMMA), polyamide (PA), polyimide (PI), cellophane, and fluorine-modified olefins (e.g., ethylene tetrafluoroethylene copolymer (ETFE), etc.). Base materials made of these materials may be used individually or two or more types may be laminated together. At least one of the front surface and the back surface of the plastic substrate may be subjected to surface treatments such as corona discharge treatment, plasma treatment, flame treatment, or solvent treatment, as needed.
[0073] The base materials 11 and 21 may be single-layer or laminated. That is, the base materials 11 and 21 may be single-layer films or laminated films. If the base materials 11 and 21 are laminated films, they may be constructed by laminating two or more films of the same type, or by laminating two or more films of different types. Examples of preferred film combinations include a combination in which a polyester film is used on the surface side of the base materials 11 and 21 and a polystyrene film or polyolefin film is used on the back side of the base materials 11 and 21, and a combination in which a cyclic polyolefin film is used on the surface side of the base materials 11 and 21 and a polyethylene film or polypropylene film is used on the back side of the base materials 11 and 21.
[0074] The thickness of the substrates 11 and 21 is preferably 5 to 100 μm, more preferably 12 to 60 μm, and even more preferably 12 to 50 μm.
[0075] <Printed layer, second printed layer> In the laminate 10, the printed layer 12 is provided on one surface of the substrate 11. In the laminate 20, the second printed layer 23 is provided on the surface opposite to the substrate 21 of the first printed layer 22, which is provided on one surface of the substrate 21. The printed layer 12 and the second printed layer 23 are printed layers formed using the ink composition of this embodiment described above. The printed layer 12, which is a printed layer formed using the ink composition, is also referred to as the "printed layer," and the second printed layer 23 is also referred to as the "second printed layer." The thickness of the printed layer 12 and the second printed layer 23 is preferably 0.2 to 3.0 μm, more preferably 0.3 to 2.0 μm, and even more preferably 0.3 to 1.5 μm.
[0076] <First printing layer> In the laminate 20, the first printed layer 22 is provided on one surface of the substrate 21. The first printed layer 22 is a printed layer (C) (hereinafter also referred to as the "color printed layer (C)") formed using an ink composition to impart design and functionality to the laminate 20. The first printed layer 22 may be a single layer or a laminated layer. The total thickness of the first printed layer 22 is preferably 0.2 to 15 μm, more preferably 0.3 to 10 μm, and even more preferably 0.3 to 8 μm.
[0077] The ink composition used to form the first printed layer 22 contains a coloring pigment. The ink composition is not particularly limited, and known compositions can be used, but examples include compositions containing a binder resin, a medium, a coloring pigment, and other components as needed. As the binder resin, any binder resin known in this field can be used. Examples of media include those previously exemplified in the description of the ink composition of the present invention. Examples of coloring pigments include organic pigments such as azo pigments (monoazo, condensed azo, etc.), slene pigments (anthraquinone, perinone, perylene, thioindigo, etc.), phthalocyanine pigments (phthalocyanine blue, phthalocyanine green, etc.), quinacridone pigments, dioxazine pigments, isoindolinone pigments, pyrrolopyrrole pigments, aniline black, and organic fluorescent pigments; and inorganic pigments such as natural products (clay, etc.), ferrocyanides (Prussian blue, etc.), sulfides (zinc sulfide, etc.), sulfates, oxides (chromium oxide, zinc oxide, iron oxide, etc.), hydroxides (aluminum hydroxide, etc.), silicates (ultramarine, etc.), carbonates, carbon (carbon black, graphite, etc.), metal powders (aluminum powder, bronze powder, zinc powder, etc.), and calcined pigments. In addition, titanium dioxide and precipitated barium sulfate, mentioned above, can also be used as coloring pigments. Other ingredients include, for example, waxes, dispersants, defoamers, lubricants, pH adjusters, and thickeners.
[0078] The printed layers of this embodiment (i.e., printed layer 12 and the second printed layer 23) may be printed layers in which the pyrolysis-type foaming agent (B) has not decomposed and foamed, or printed layers in which the pyrolysis-type foaming agent (B) has decomposed and foamed. The decomposition and foaming of the pyrolysis-type foaming agent (B) can be carried out by heating the printed layers. The heating temperature is preferably 0 to 50°C higher than the decomposition temperature of the pyrolysis-type foaming agent (B), more preferably 5 to 40°C higher, and even more preferably 10 to 30°C higher. For example, the heating temperature is preferably 100 to 200°C, more preferably 110 to 180°C, and even more preferably 120 to 160°C.
[0079] <Method for manufacturing laminates> The manufacturing method for the laminate 10 shown in Figure 1 includes the step of forming a printed layer 12 on one surface of the substrate 11 using the ink composition of this embodiment. The manufacturing method for the laminate 20 shown in Figure 2 includes the steps of (1) forming a first printed layer 22 on one surface of a substrate 21 using an arbitrary ink composition, and (2) forming a second printed layer 23 on the surface of the first printed layer 22 opposite to the substrate 21 using the ink composition of this embodiment.
[0080] In the manufacturing method of the laminate 10 shown in Figure 1, for example, the ink composition of this embodiment is applied to one surface of the substrate 11 and dried to form the printed layer 12. Alternatively, the ink composition may be applied to one surface of the substrate 11, dried to form a printed layer 12, and then another layer of the ink composition may be applied (overcoated).
[0081] The method of coating the ink composition is not particularly limited, and known coating methods such as gravure printing, flexographic printing, brush coating, gravure coater method, die coater method, bar coater method, spray coating method, flow coating method, dip coating method, spin coating method, and curtain coating method can be used. Among these, gravure printing and flexographic printing are suitable because they have excellent drying properties and can be used for high-speed printing.
[0082] The drying method is not particularly limited as long as it can remove the medium contained in the ink composition coated on one surface of the substrate 11, but examples include vacuum drying, pressure drying, heat drying, and air drying. The heating temperature is preferably 30 to 150°C, and more preferably 40 to 120°C.
[0083] The manufacturing method for the laminate 20 shown in Figure 2 includes the above steps (1) and (2) in this order. In step (1), for example, an arbitrary ink composition is applied to one surface of the substrate 21 and dried to form a first printed layer 22. In step (2), for example, the ink composition of this embodiment is applied to the surface of the first printed layer 22 opposite to the substrate 21 and dried to form a second printed layer 23. Step (1) may be performed once or two or more times. In other words, any ink composition may be applied in multiple layers. Step (2) may be performed once or two or more times. In other words, the ink composition of this embodiment may be applied in multiple layers. The coating method and drying method in steps (1) and (2) can be the same as those used for manufacturing the laminate 10.
[0084] <Application> The applications of the ink composition of this embodiment are not particularly limited, but are suitable, for example, for flexible packaging and industrial materials. Here, "flexible packaging" refers to packaging materials made of flexible materials, i.e., flexible packaging, which is used for packaging food, daily necessities, and other items. [Examples]
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples unless it exceeds the gist of the invention.
[0086] [Raw materials used] <Binder resin (A)> ((Meth)acrylic resin (A1)) A1-1: (Meth)acrylic resin, manufactured by Taisei Fine Chemical Co., Ltd., product name "Acrit 1LO-846", solid content: 40% by mass, glass transition temperature: 60.2℃, hydroxyl value: 8.6 mg KOH / g, acid value: 13.05 mg KOH / g. A1-2: (Meth)acrylic resin, manufactured by Taisei Fine Chemical Co., Ltd., product name "Acrit 6BF-400", solid content: 41% by mass, glass transition temperature: 23.9℃, hydroxyl value: 29.7 mgKOH / g, acid value: 2.41 mgKOH / g. A1-3: (Meth)acrylic urethane resin, manufactured by Taisei Fine Chemical Co., Ltd., product name "Acrit 8UA-017", solid content: 48.5% by mass, acid value: 10.5 mg KOH / g.
[0087] (Other resins (A2)) A2-1: Vinyl chloride-vinyl acetate copolymer, manufactured by Nisshin Chemical Industry Co., Ltd., product name "Solvine TA5R", solid content: 100% by mass, softening temperature: 72°C, glass transition temperature: 78°C. A2-2: Vinyl chloride-vinyl acetate copolymer, manufactured by Nisshin Chemical Industry Co., Ltd., product name "Solvine TA3", solids content: 100% by mass, softening temperature: 67°C, glass transition temperature: 65°C. A2-3: Polyurethane resin, manufactured by Sunopco Corporation, product name "Sunprene IB-501", solids content: 30% by mass, softening temperature: 130℃, glass transition temperature: -24℃.
[0088] <Thermolytic foaming agent (B1)> B1-1: 4,4'-Oxybis(benzenesulfonylhydrazide) (OBSH), manufactured by Eiwa Chemical Industries, Ltd., product name "NeoCelbon N#1000M", solids content: 100% by mass, average particle size: 4 μm. B1-2: Azodicarbonamide (ADCA), manufactured by Eiwa Kasei Kogyo Co., Ltd., product name "Vinihole AC#3C-K2", solid content: 100% by mass, average particle size: 5 μm. B1-3: N,N'-Dinitrosopentamethylenetetramine (DPT), manufactured by Eiwa Kasei Kogyo Co., Ltd., product name "Cellular D", solids content: 100% by mass, average particle size: 18 μm. B1-4: Azodicarbonamide (ADCA), manufactured by Eiwa Kasei Kogyo Co., Ltd., product name "Vinihole AC#R", solid content: 100% by mass, average particle size: 25 μm.
[0089] <Thermolytic foaming agent (B2)> ·B2-1: Manufactured by Eiwa Kasei Kogyo Co., Ltd., product name "Cell Paste 101", solid content: 100% by mass.
[0090] • B-1: A mixture of the above-mentioned pyrolysis-type foaming main agent B1-1 and the above-mentioned pyrolysis-type foaming aid B2-1 (mass ratio = 1:1), decomposition temperature: 127°C. • B-2: A mixture of the above-mentioned pyrolysis-type foaming main agent B1-2 and the above-mentioned pyrolysis-type foaming aid B2-1 (mass ratio = 1:1), decomposition temperature: 148℃. • B-3: A mixture of the above-mentioned pyrolysis-type foaming main agent B1-3 and the above-mentioned pyrolysis-type foaming aid B2-1 (mass ratio = 1:1), decomposition temperature: 142℃. • B-4: A mixture of the above-mentioned pyrolysis-type foaming main agent B1-4 and the above-mentioned pyrolysis-type foaming aid B2-1 (mass ratio = 1:1), decomposition temperature: 148℃. • B-5: Only the above-mentioned pyrolysis-type foaming agent B1-1 is used (no pyrolysis-type foaming aid), decomposition temperature: 160℃.
[0091] <Optional ingredients> C-1: Hydrocarbon wax, manufactured by Mitsui Chemicals, Inc., product name "High Wax 220P", penetration: 13. C-2: Defoaming agent, manufactured by BYK, product name "BYK-1751". C-3: Hardener, manufactured by Mitsui Chemicals, Inc., product name "Takenate D-160N".
[0092] • C-4: Medium (a mixed solvent of ethyl acetate and isopropanol in a 3:1 (mass ratio) ratio).
[0093] [Examples 1-17, Comparative Examples 1-6] <Preparation of Ink Composition> According to the compositions shown in Tables 1 and 2, the binder resin (A), the pyrolysis-type foaming agent (B), the medium, and any optional components were mixed, and the resulting mixture was kneaded in a paint shaker to obtain an ink composition. The units of the numerical values for each component in Tables 1 and 2 are parts by mass, and except for the medium, they represent the amount of solids. Blank spaces in Tables 1 and 2 mean that the component was not included. The content of pyrolysis-type foaming agent (B) in Tables 1 and 2 refers to the content of the solids of the pyrolysis-type foaming agent (B) relative to the total mass of solids (excluding the medium) of the ink composition. The content of resins with a softening temperature of 70°C or less in Table 1 refers to the content of the solids of resins with a softening temperature of 70°C or less relative to the total mass of solids of the binder resin (A).
[0094] <Creating printed materials> The prepared ink composition was diluted using the same medium as that used in the formulation so that its viscosity at 25°C, as measured using a Zahn cup #3, was 17 seconds, thereby preparing a printing ink. The prepared printing ink was applied to the surface of a PET film (manufactured by Toyobo Co., Ltd., product name "E5102", thickness: 25 μm) using a bar coater #20. The film was then dried at 50°C for 10 seconds to produce a printed material.
[0095] <Heat treatment> The resulting printed materials were subjected to heat treatment by being left to stand for 20 minutes in a dryer set to the decomposition temperature of the thermally decomposed foaming agent (B) contained in each material + 10°C.
[0096] <Evaluation of heat retention> The printed material, after heat treatment, was wrapped around a 6cm diameter glass bottle with the printed side facing inward, and preheated to 100°C. Next, the glass bottle was taken out into a 20°C room, and boiling water was poured into it up to the top. Then, the surface temperature of the wrapped printed material was measured using a non-contact thermometer, and the time required to go from 80°C to 50°C was measured. The results were compared with those of a blank (wrapped only with PET film), and the heat retention performance was evaluated according to the evaluation criteria shown below. A score of 3 to 5 is considered passing. 5. The difference in time taken compared to the blank period was 3 minutes or more. 4. The difference in time taken compared to the blank period was between 2 minutes and 3 minutes. 3. The difference in time taken compared to the blank period was between 1 minute and 2 minutes. 2. The difference in time taken compared to the blank period was 30 seconds or more, but less than 1 minute. 1: The difference in time taken compared to the blank period was less than 30 seconds.
[0097] <Evaluation of abrasion resistance> Before heat treatment, printed materials were subjected to an abrasion resistance test using a JSPS-type friction fastness tester (manufactured by Tester Sangyo Co., Ltd., product name "AB-301") by rubbing the printed surface 100 times back and forth with a black cloth (metal width 3) under a load of 200 gf. Afterwards, the appearance of the printed layer was visually inspected, and the abrasion resistance was evaluated according to the evaluation criteria shown below. A score of 3 to 5 is considered acceptable. 5: The area of the printed layer that has migrated to the black cloth (gold cloth No. 3) is less than 5%. 4. The percentage of the printed layer area that has migrated to the black cloth (gold cloth No. 3) side is 5% or more and less than 10%. 3: The percentage of the printed layer area that has migrated to the black cloth (gold cloth No. 3) side is 10% or more and less than 30%. 2: The area of the printed layer that has moved to the black cloth (gold cloth No. 3) side is 30% or more and less than 50%. 1: The area of the printed layer that has migrated to the black cloth (gold cloth No. 3) is 50% or more.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] The printed coatings formed from the ink compositions of Examples 1 to 17 were found to have excellent abrasion resistance and heat retention properties. The printed coatings formed from the ink compositions of Comparative Examples 1 and 2, which contained a low amount of the thermal decomposition type foaming agent (B), did not generate sufficient bubbles upon heat treatment and exhibited poor heat retention. On the other hand, the printed coatings formed from the ink compositions of Comparative Examples 3 and 4, which contained a high amount of the thermal decomposition type foaming agent (B), exhibited poor abrasion resistance. In the ink compositions of Comparative Examples 5 and 6, which contained a large amount of binder resin (A) with a softening point of 70°C or lower, the printed coatings formed from these compositions showed that although sufficient amounts of thermally decomposed foaming agent (B) and foam-derived bubbles were generated by the heat treatment, these bubbles were filled in by the softened binder resin (A), resulting in poor heat retention. [Industrial applicability]
[0102] The printed coating formed from the ink composition of the present invention is useful because it has excellent abrasion resistance and excellent heat retention. [Explanation of Symbols]
[0103] 10 Laminate 11 Base material 12 printing layer 20 Laminate 21 Base material 22. First printing layer (color printing layer (C)) 23 Second printing layer
Claims
1. An ink composition comprising a binder resin (A) and a thermal decomposition type foaming agent (B), The pyrolysis-type blowing agent (B) contains the pyrolysis-type main blowing agent (B-1), The solid content of the thermal decomposition type foaming agent (B) relative to the total mass of solid content of the ink composition is 5 to 65% by mass. The binder resin (A) includes (meth)acrylic resin (A1), An ink composition in which the solid content of a resin with a softening temperature of 70°C or lower is 50% by mass or less, relative to the total mass of solid content of the binder resin (A).
2. Furthermore, the ink composition according to claim 1 further contains a curing agent.
3. The ink composition according to claim 1, wherein the average particle size of the thermal decomposition type foaming agent (B-1) is 20 μm or less.
4. Furthermore, the ink composition according to claim 1, further comprising a hydrocarbon wax.
5. An ink composition according to any one of claims 1 to 4, which is for gravure printing or flexographic printing.
6. A laminate comprising a plastic film and a printed layer formed on one surface of the plastic film using the ink composition described in claim 5.
7. The laminate according to claim 6, wherein the printed layer is a printed layer in which the thermal decomposition type foaming agent (B) has not decomposed and foamed.
8. The laminate according to claim 6, wherein the printed layer is a printed layer obtained by the decomposition and foaming of the thermal decomposition type foaming agent (B).
Citation Information
Patent Citations
Liquid print ink, printed matter, and packaging material
JP2021066817A